La jamaʿat al Tabligh en Asie centrale : réactivation des liens islamiques avec le sous continent indien et insertion dans un islam mondialisé - Bayram Balci (Revue des Mondes Musulmans et de la Méditerranée)
After two centuries of close relationships, especially under the Mughals, Islamic ties between India and Central Asia were considerably weakened after the Tsarist colonization and the subsequent Soviet religious repression and ideological isolation. However, when Central Asian post-Soviet republics became independent in 1991, they renewed all kinds of links with the Indian subcontinent. And the revival of Central Asian Islam benefited from international sources of Islamic inspiration from Turkey, the Arab countries as well as from India. The last one drew less attention from analysts than the other sources of influence, although it has gained ground through the past years all over the region with a particular highlight in Kazakhstan and Kyrgyzstan, where the India-based Jamaʿat al Tabligh has met with a significant success. This Islamic organization established in British India in the 1920s defines itself as a non-radical and non-political movement, promoting a "basic" Islamic faith and practice. So far, the Jamaʿat al Tabligh has been, in fact, tacitly supported by local authorities who would rather use them as a shield against more radical Islamic groups who openly oppose the established regime.